Result of electrophysiological study in patients with undocumented suspected paroxysmal supraventricular tachycardia: the BELIEVE-SVT registry. (24th May 2021) - Ramos Jimenez, J; Marco Del Castillo, A; Lozano Granero, VC; Ramos Fernandez, P; Jimenez Sanchez, D; Gunturiz Beltran, C; Alonso Fernandez, P; Ayala, HD; Dallaglio, P; Salgado, R; Lazaro Rivera, C; Rodriguez Manero, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Paroxysmal supraventricular tachycardias (PSVT) are common arrhythmias and catheter ablation is considered its first-line treatment. However, the duration of the episodes frequently precludes ECG documentation. Thus, patients may not be referred for ablation until the tachycardia is documented, leading to recurrences, emergency room visits and often unnecessary tests or treatments. Our objective was to evaluate the results of electrophysiological study (EPS) followed or not by ablation in patients with suspected but not documented PSVT. Methods: Multicenter, retrospective, observational registry of consecutive patients undergoing EPS due to clinical suspicion of PSVT, but with no prior ECG documentation. Collection of clinical and EPS data, along with data regarding ablation, when performed. Results: 427 patients of 12 centers were included. Mean age was 46.3 ±16.1 and 297 (69.6%) were females. Most frequent symptoms consisted on sudden onset (n = 360; 84.9%) and abrupt end (n = 304; 72.0%), with median episode duration of 10 minutes (interquartile range 5-20 min). Sustained arrhythmias were induced in most patients (n = 255; 59.7%). Specific types are summarized in Table 1. Ablation was performed in 274 (64.2%) patients. A total of 10 complications (2.3% of procedures) were reported: 3 transient AV block, 2 PR interval prolongation, 2 puncture-related hematoma, 2 painful site of puncture and 1 catheter entrapment in mitral chordae. Conclusions Electrophysiological study in patients with palpitations highly suggestive of PSVT is an effective and safe diagnostic and therapeutic tool that may be considered as a first-choice even in the absence of documented tachycardia.